Življenjsko okolje ustvarjalnih ljudi v Sloveniji - Kozina, Jani (Geografija Slovenije, 2016)
Living environment of creative people in SloveniaThe book attempts to answer two key questions: where do creative people reside in Slovenia and why do they choose to live there. The findings show that creative people in Slovenia adhere to a similar percentage of the work force as in other highly developed countries~this is also the occupational group that has increased in number the most compared to others in the last decade. The spatial distribution analyses show that, similar to other countries, creative people in Slovenia are unevenly distributed. A lower concentration is typical predominantly for economically less developed regions in Eastern Slovenia, while a higher concentration occurs in more developed regions of Western Slovenia. With time, the differences between the regions increase, but decrease within the regions themselves. Contemporary settlement processes run towards a deconcentration from heavily urbanized settlement types to more sparsely populated suburbanized and rural settlements. The most important spatial distribution factors for creative people in Slovenia are: living environment quality with a great emphasis on access to nature, identity or close connections to people and places, and workplace proximity. Additionally, some important differences were identified from the aspect of the selected regionalization as well as the settlement urbanization level.